The Resistance against Racism: A Critical Discourse Analysis of Anti-Asian Racism Relating to Covid-19 Outbreak - Fadhila Hananta Putri; Andi Muhammad Irawan (Universitas Negeri Padang, 2022)
This study is aimed to find out (1) the discourse topics and (2) the discourse strategies from the utterances produced by Asian-Americans as the victim of the racist attack during the Covid-19 outbreak to reveal how they voice their ideologies in defending themselves and maintaining their existence in society. The researcher employs a qualitative method considering the data are in the form of written-text and also analyse the humanities and social sciences. Specifically, the researcher analysed the discourses presented in several videos from YouTube that being transcribed into written discourses. This study focuses on how Asian-Americans portray themselves and others in their discourses based on their beliefs. From seven videos being analysed, the researcher has collected 80 data that consist of the Positive-Self and Negative-Others presentation. By utilizing Van Djik’s Ideological Square, the researcher found out there are 16 discourse topics implied in Asian-Americans’ utterances, such as ‘We are also Americans’, ‘Anti-Asian-Americans is terrifying’, etc. Furthermore, there are 22 discourse strategies used by Asian-Americans in defending themselves. The study reveals Asian-Americans as the racist-victim attempt to emphasize the Anti-racism movement. Moreover, the researcher has found that several discourses consist of negative-attitude towards majorities or Americans society.